2011
DOI: 10.1210/en.2011-1295
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Coupling Increased Hexosamine Biosynthesis Pathway Activity to Membrane Cholesterol Toxicity and Cortical Filamentous Actin Derangement Contributing to Cellular Insulin Resistance†

Abstract: Hyperinsulinemia is known to promote the progression/worsening of insulin resistance. Evidence reveals a hidden cost of hyperinsulinemia on plasma membrane (PM) phosphatidylinositol 4,5-bisphosphate (PIP(2))-regulated filamentous actin (F-actin) structure, components critical to the normal operation of the insulin-regulated glucose transport system. Here we delineated whether increased glucose flux through the hexosamine biosynthesis pathway (HBP) causes PIP(2)/F-actin dysregulation and subsequent insulin resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…In line with increased HBP activity transcriptionally provoking a membrane cholesterol‐based insulin‐resistant state, we found that HBP inhibition attenuated the transcription and expression of genes involved in cholesterol synthesis ( e.g., Hmgcr ) and prevented membrane cholesterol accumulation, F‐actin loss, and GLUT4/glucose transport dysfunction (Bhonagiri et al. 2011; Habegger et al. 2012a; Penque et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with increased HBP activity transcriptionally provoking a membrane cholesterol‐based insulin‐resistant state, we found that HBP inhibition attenuated the transcription and expression of genes involved in cholesterol synthesis ( e.g., Hmgcr ) and prevented membrane cholesterol accumulation, F‐actin loss, and GLUT4/glucose transport dysfunction (Bhonagiri et al. 2011; Habegger et al. 2012a; Penque et al.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that increased hexosamine biosynthesis pathway (HBP) activity in fat/muscle cells increases O‐linked N‐acetylglucosamine modification of the transcription factor Sp1, leading to transcriptional activation of HMG‐CoA reductase, the rate‐limiting enzyme in cholesterol biosynthesis (Bhonagiri et al. 2011; Habegger et al. 2012a; Penque et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aberrantly increased plasma membrane cholesterol is seen uniformly in insulin-resistant mice, rats, swine, and humans, and normalization restores insulin responsivity. [1][2][3][4] Mechanistic studies in clonal cells, as well as in fat and skeletal muscle tissue demonstrate that excess plasma membrane cholesterol reduces cortical filamentous actin (F-actin), which is essential for glucose transporter type 4 (GLUT4) regulation by insulin. In addition to this negative consequence of excess plasma membrane cholesterol on insulin action, Llanos et al found the ryanodine receptor calcium signals, which are important for GLUT4 regulation, are negatively affected by increased skeletal muscle membrane cholesterol.…”
mentioning
confidence: 99%